Investigate the sexual habits of young people: a cross-sectional study among nursing students of the University of Palermo - Provenzano, Sandro; Santangelo, Omar Enzo; Terranova, Antonio; D'Anna, Giuseppe; Grigis, Dimple; Firenze, Alberto (Acta Biomedica Atenei Parmensis, 2020)
Introduction: Sexually transmitted diseases are an emerging problem especially among young people, increasing the burden of disease in this population. The aim of the study was to evaluate sexual habits, sexual relations and knowledge of STIs among the students in the nursing science course of the University of Palermo. Materials and Methods: In April 2019, a survey was provided to students that investigate on: personal information and habits, knowledge of sexually transmitted diseases, anti-HPV vaccination. Multivariable logistic regression was performed, considering it as a dependent variable “Have you occasionally had unprotected sex (without a condom)? Yes”, in order to evaluate the role of the variables of the questionnaire. Results are expressed as adjusted Odds Ratio (aOR). Results: 405 students completed the questionnaire. The mean age of the sample is 21.65 years, 69.63% of the interviewees are women. The multivariable logistic regression shows that the risk of having occasional unprotected sex (without condom) is significantly associated with “Do you permanently have unprotected sex (without a condom)? Yes” (aOR 4.46); “Have you ever received information on sex education and/or sexually transmitted diseases? No” (aOR 6.02); “Age Class <22 years old (aOR 2.03); “Number of sexual partners: As the unit increase” (aOR 1.18). Conclusions: Too many young people receive confusing and conflicting information about relationships and sex, as they make the transition from childhood to adulthood. Nurses play an important role in promoting public health. The study showed that young students are not still enough sensitized on sexually transmitted infections and preconception care.(www.actabiomedica.it)